A few notes on the grammatical norm of the Peter’s the Great epoch (On the 80th anniversary of N.I. Gainullina) (Eurasian Journal of Philology Science and Education, 2019)
On the material of syllabic poetry of Peter’s epoch the author develops the ideas of N. I. Gainullinaon the essence of the language norm of the transition period. The main attention is paid to the peculiarities of the functioning of modaltemporal forms in texts belonging to different stylistic registers. Theauthor comes to the conclusion that normative thinking is peculiar to the best writers of the epoch. Theselection and organization of language means in their works is conscious.